Analisis Usability Aplikasi Mobile Kampung Merah Putih Menggunakan Metode Heuristics Evaluation - Kalingga Cahya Sumirat, Gilang; Rusdi, Ibnu (Smart Comp :Jurnalnya Orang Pintar Komputer, 2023)
The Kampung Merah Putih mobile application is one of the works of the nation's children that deserves respect. For some developed countries, smart applications may be familiar, but for Indonesians who tend to want practicality in everything, it is a very interesting thing. The Kampung Merah Putih application is an application created to facilitate environmental management. The satisfaction of Kampung Merah Putih application users needs to be evaluated using the Heuristic Evaluation method with the hope that application users can always be satisfied with its features. Data will be analyzed using quantitative methods with descriptive statistics and inferential statistics. Collecting data by distributing questionnaires online with the sample used is active users for at least one month of use. The result shows the tendency of respondents to agree with the items asked in the Heuristic Evaluation of 80% of the total answers. However, there are many regression modeling results on the T-test that need attention for further evaluation, namely the dimensions of Visibility of System Status, User Control and Freedom, Consistency and Standard, and Recognition Rather Than Recall Help and Documentation.